2021
DOI: 10.1016/j.urology.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Deferring Elective Urologic Surgery During the COVID-19 Pandemic: The Patients’ Perspective

Abstract: Objectives To explore the perspective of urological patients on the possibility to defer elective surgery due to the fear of contracting COVID-19. Methods All patients scheduled for elective urological procedures for malignant or benign diseases at two high-volume Centres were administered a questionnaire, through structured telephone interviews, between 24 th and 27 th April 2020. The questionnaire included three qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
1
26
0
2
Order By: Relevance
“…Widespread reports indicate that even when services have been re-established, patients have been reluctant, and afraid to take up scheduled appointments [9][10][11]. Hospitals have put a number of mitigations in place: COVID-19 testing programmes for patients and staff; separating emergency and planned elective patient cohorts from each other; enhanced cleaning programmes; restricting access to hospital sites including access for patient visitors; requiring patients to self-isolate for up to 14 days before a procedure or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread reports indicate that even when services have been re-established, patients have been reluctant, and afraid to take up scheduled appointments [9][10][11]. Hospitals have put a number of mitigations in place: COVID-19 testing programmes for patients and staff; separating emergency and planned elective patient cohorts from each other; enhanced cleaning programmes; restricting access to hospital sites including access for patient visitors; requiring patients to self-isolate for up to 14 days before a procedure or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Such information is necessary for training health care workers to develop psychological skills for helping patients who experience worry, anxiety, and other emotional problems. It is also necessary to investigate how the COVID-19 pandemic affects people’s reactions when they or a person close to them needs to be hospitalized to undergo surgery for treating an illness [ 11 , 12 ]. Studies have shown that the COVID-19 pandemic poses a considerable challenge to routine medical services.…”
Section: Introductionmentioning
confidence: 99%
“…Such information is necessary for training health care workers to develop psychological skills for helping patients who experience worry, anxiety, and other emotional problems. It is also necessary to investigate how the COVID-19 pandemic affects people's reactions when they or a person close to them needs to be hospitalized to undergo surgery for treating an illness [11,12]. Studies have shown that the COVID-19 pandemic poses a considerable challenge to routine medical services.…”
Section: Introductionmentioning
confidence: 99%